Compositional variations for small-scale gamma prime (γ′) precipitates formed at different cooling rates in an advanced Ni-based superalloy. (15th February 2015) - Chen, Y.Q.; Francis, E.; Robson, J.; Preuss, M.; Haigh, S.J.
Abstract: Size-dependent compositional variations under different cooling regimes have been investigated for ordered L12 -structured gamma prime (γ′) precipitates in the commercial powder metallurgy Ni-based superalloy RR1000. Using scanning transmission electron microscope imaging combined with absorption-corrected energy-dispersive X-ray spectroscopy, we have discovered large differences in the Al, Ti and Co compositions for γ′ precipitates in the size range 10–300 nm. Our experimental results, coupled with complementary thermodynamic calculations, demonstrate the importance of kinetic factors on precipitate composition in Ni-based superalloys. In particular, these results provide new evidence for the role of elemental diffusion kinetics and aluminium antisite atoms on the low-temperature growth kinetics of fine-scale γ′ precipitates. Our findings have important implications for understanding the microstructure and precipitation behaviour of Ni-based superalloys, suggesting a transition in the mechanism of vacancy-mediated diffusion of Al from intrasublattice exchange at high temperatures to intersublattice antisite-assisted exchange at low temperatures.